2020
DOI: 10.1108/medar-08-2019-0540
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory vs voluntary exercise on non-financial reporting: does a normative/coercive isomorphism facilitate an increase in quality?

Abstract: Purpose This paper aims at investigating the quality of non-financial reporting (NFR) in light of Directive no. 2014/95/EU. Specifically, it focuses on the quality of NFR in Italian companies, as required by Legislative Decree no. 254/2016. Design/methodology/approach The method used to develop the analysis is mainly qualitative. A content analysis of 184 non-financial reports (NFRs) was conducted on a sample of 92 companies that have been previously involved in the process of NFR on a voluntary basis. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 67 publications
0
69
2
1
Order By: Relevance
“…On the contrary, Korca et al (2021) found a significant increase in the quantity but not in the quality of NFI. Other authors, instead, did not find a decisive influence of the Directive on disclosure levels (Carungu et al 2020;Nicolò et al 2020). Postimplementation analyses focused on subtopics of NFI, identifying a positive association between the quality of nonfinancial risk information and market value (Veltri et al 2020), showing that corporate governance and report characteristics affect environmental information (Caputo et al 2021), and revealing high heterogeneity in the quality of SDG reporting (Pizzi et al 2021).…”
Section: Literature Reviewmentioning
confidence: 92%
“…On the contrary, Korca et al (2021) found a significant increase in the quantity but not in the quality of NFI. Other authors, instead, did not find a decisive influence of the Directive on disclosure levels (Carungu et al 2020;Nicolò et al 2020). Postimplementation analyses focused on subtopics of NFI, identifying a positive association between the quality of nonfinancial risk information and market value (Veltri et al 2020), showing that corporate governance and report characteristics affect environmental information (Caputo et al 2021), and revealing high heterogeneity in the quality of SDG reporting (Pizzi et al 2021).…”
Section: Literature Reviewmentioning
confidence: 92%
“…The quality of non-financial reports (NFRs) is the focus of the paper by Jonida Carungu, Roberto Di Pietra and Matteo Molinari (Carungu et al , 2021), in a scenario where NFR became mandatory under the European Directive no. 2914/95/EU implemented in Italy.…”
Section: Framing the Papers Included In The Special Issue On New Challenges In Sustainability Reportingmentioning
confidence: 99%
“…Many investors, especially those more concerned about the economic effects of climate risks, share the view that climate risk reporting should be mandatory and standardized, as is currently the case with financial reporting . This view is shared by La Torre et al (2018), Lombard and Secundo, (2020), La Torre (2020), andCarungu et al (2020), who, respectively, point to the need to structure and digitize the non-financial information and to increase its reliability and comparability.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Secondly, non-financial reports, though they constitute an essential tool in the process of legitimization of corporate social responsibility (Schuman, 1995;O' Donovan, 1999;Zyznarska-Dworczak, 2015), are not widely applied to disclose climate-related information (Giannarakis et al, 2018, Kouloukoui et al, 2018Wassim, 2019). Also, in many authors' opinions, the scope of information disclosed in the reports is insufficient to meet the stakeholders' expectations (Da Silva Gomes et al, 2017;Leurig and Dlugolecki, 2013;Leurig, 2011;Broder, 2010;Ben-Amar and McIlkenny, 2014). What is the situation in Poland?…”
Section: Introductionmentioning
confidence: 99%